2019
DOI: 10.7717/peerj.6603
|View full text |Cite
|
Sign up to set email alerts
|

Pain neuroscience education on YouTube

Abstract: Objectives The Internet in general, and YouTube in particular, is now one of the most popular sources of health-related information. Pain neuroscience education has become a primary tool for managing persistent pain, based in part on the discovery that information about pain can change pain. Our objective was to examine the availability, characteristics, and content of YouTube videos that address the neuroscience of pain. Methods We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 36 publications
0
25
0
6
Order By: Relevance
“…As the quality of online information is not always sufficiently good, it is advisable to recommend helpful and scientifically sound sources for educational videos and discuss the content with patients. In a systematic review about pain education videos on YouTube, Heathcote and colleagues [ 85 ] identified over one hundred pain education videos in English, some of them of good quality and useful for delivering pain education in clinical practice.…”
Section: Which Methods Are Helpful For Delivering Pain Education?mentioning
confidence: 99%
“…As the quality of online information is not always sufficiently good, it is advisable to recommend helpful and scientifically sound sources for educational videos and discuss the content with patients. In a systematic review about pain education videos on YouTube, Heathcote and colleagues [ 85 ] identified over one hundred pain education videos in English, some of them of good quality and useful for delivering pain education in clinical practice.…”
Section: Which Methods Are Helpful For Delivering Pain Education?mentioning
confidence: 99%
“…Pain science education is commonly part of multidisciplinary pain treatment [70] and can utilize freely available online resources [25] that complement pain science education/communication which is typically individually-tailored and thereby primarily delivered by a therapist. Additionally, PNE4Kids, a pain science curriculum for children (6–12 years old), has recently been developed [27] and is freely available for clinicians at .…”
Section: State Of the Art Of Rehabilitation For Pediatric Chronic mentioning
confidence: 99%
“…In addition, Visual Analog Scale, Numeric Pain Rating Scale, Pressure Pain Threshold, Pain Disability Index, Pain Catastrophizing Scale were used in selected studies to investigate the effect on pain. All studies selected had a positive effect of PNE compared to the control except for only one study (Table 1) [28][29][30][31][32][33][34][35].…”
Section: Pain Neuroscience Education On Kinesiophobia and Pain For Chmentioning
confidence: 99%